Investigations on an Injector for a Low Pressure Hydrogen Direct Injection - Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2014)
Hydrogen engines represent an economic alternative to fuel cells for future energy scenarios based on Liquid Organic Hydrogen Carriers (LOHC). This scenario incorporates LOHCs to store hydrogen from fluctuating renewable energy sources and deliver it to decentralised power generation units. Hydrogen engines were deeply investigated in the past decade and the results show efficiencies similar to CI engines. Due to the low energy density and tendency towards pre-ignition of hydrogen, the key element to reach high efficiency and a safe operation is a direct injection of the hydrogen. Because high injection pressure is not available in practical applications or would reduce the possible driving range, a low injection pressure is favourable. The low density leads to large flow cross sections inside the injector, similar to CNG direct injectors. So far, some research CNG and hydrogen low pressure direct injectors were investigated, but no commercial injector is available. The objective of this work is the development of a low pressure hydrogen direct injector, with the ability to run unlubricated in neat hydrogen and meeting the necessary flow rate for a stationary engine generating 7.5 kW per cylinder at 1500 rpm. To characterize the injector an injector test stand with coriolis mass flow meter and a needle lift measurement through laser triangulation was used. Supported by the results of the test stand an injector was build, meeting the mentioned requirements. The final design is based on a commercial available injector with modifications on the injector controller, the needle actuation and special surface treatments. The injector was bench tested under dry conditions for over 100 million cycles without failure or critical wear marks. The required mass flow rate was achieved at a relatively low pressure of 850 kPa, compared to prior publications. This low injection pressure is especially advantageous for engines running on LOHC based hydrogen, which is released at near ambient pressure and must be compressed before injection, reducing the systems overall efficiency. The presented injector will be used in a small hydrogen heat and power generation unit, which is part of a LOHC energy storage demonstrator project currently investigated by the BavarianHydrogen Center, a joint project of five Bavarian universities.
Created from Fastlane, Scopus look-up